Is 18F-FDG PET/CT Beneficial for Newly Diagnosed Breast Cancer Patients With Low Proportion of ER Expression? - Liu, Jiachen; Sun, Runlu; Yin, Yuping; Li, Jingyan; Liu, Xuming; Liu, Sheng; Zhang, Zhanlei; Hu, Jieting; Wan, Xiaoting; Zhang, Hong (Frontiers in Oncology, 2021)
Objective It is unclear whether the receptor status of breast malignancy or the proportion of receptors expression is useful in the interpretation of 18F-FDG PET/CT. This study’s purpose was to analyze whether 18F-FDG PET/CT was valuable for helping newly diagnosed breast cancer patients find suspected or unsuspected metastasis lesions based on the proportion of receptors expression. Materials and Methods Eighty newly diagnosed breast cancer patients were divided into six groups, containing N0 (no extraaxillary lymph node metastasis), N1 (extraaxillary lymph node metastasis), M0 (no distant metastasis), and M1 (distant metastasis) groups, C0 (no unsuspected metastasis), and C1 (unsuspected metastasis and treatment plan changed) detected by PET/CT. The main data, including the proportion of receptors ER (estrogen receptor), PR (progesterone receptor), and Her-2 (human epidermal growth factor receptor 2) status, were extracted. Simple correlation and logistic regression were preformed to analyze the association between them. Results Patients in N1 group had lower proportion of ER (%) and PR (%) than that in N0 group (ER: 2 [0–80] vs. 80 [15–95]; PR: 1 [0–10] vs. 20 [0–45], p<0.001). Moreover, the proportions of ER and PR were negatively correlated with N1 (ER: [r= −0.339, p= 0.002], PR: [r= −0.247, p= 0.011]) by simple correlation. Also, patients in C1 group had lower proportion of ER (%) and PR (%) than those in C0 group (ER: 10 [0–85] vs. 80 [15–90], p=0.026; PR: 1 [0–10] vs. 20 [0–70], p=0.041), while the distribution of ER and PR between M1 and M0 group had no significant difference. After the adjustment of traditional factors, the negative correlation between the proportion of ER (OR=0.986, 95% CI of OR [0.972–0.999], p=0.016) and C1 was found by logistic regression, cutoff value was 25% (ER) calculated by ROC (Receiver Operating Characteristic) curve (AUC [Area Under Curve]= 0.647, p=0.024). Conclusion The proportion of ER in newly diagnosed breast cancer was negatively correlated with unsuspected metastasis detected by 18F-FDG PET/CT. 18F-FDG PET/CT might be recommended for newly diagnosed breast cancer patients with single lesions when the ER expression proportion is less than 25% to find unsuspected metastasis lesions and to modify treatment plan contrasted with conventional imaging and clinical examination.